New Zealand residential subdivision and development controls in the context of sustainable development : a thesis in fulfilment of course requirements for the Degree of Master of Resource and Environmental Planning at Massey University - Hills, Richard Leighton Roy (Massey University, 1998)
Recent decades have seen an increased realisation by humanity that the resources of the Earth are not inexhaustible. International conferences have discussed ways in which the resources of the Earth can be better managed, giving rise to the term "sustainable development". Since 1991 New Zealand local authorities have been drafting new plans to achieve the 'sustainable management of resources'. However, with the population of New Zealand becoming increasingly urbanised, greater attention needs to be paid as to whether the ways in which urban areas develop are sustainable. A benchmark needs to be established, against which New Zealand planning controls can be compared to find out how effective those controls are in encouraging sustainability, and pinpoint those areas where improvement is needed. This research identifies those factors which are generally thought to be important in achieving more sustainable forms of residential subdivision and development, and investigates whether indeed the new Plans which are being developed incorporate provisions which are consistent with those factors. A series of indicators were developed, aimed principally at checking new plan provisions for their consistency with those factors which were thought to assist in bringing about more sustainable forms of residential subdivision and development. The reported research results found that experts in the field of sustainable development generally felt that sustainable residential subdivision and development avoided locating in areas of high ecological significance, hazards, or high soil value, promoted a more compact, energy-efficient urban form, made the most efficient use of infrastructure and minimised pollution, minimised the use of non-renewable resources, and helped reduce crime. New Zealand planning controls were generally found to be slightly more sustainable than unsustainable when measured on a continuum. While this may be seen as positive, the fact remains that, there is still much room for improvement. Some of the reasons for the gap between New Zealand residential subdivision and development controls and the ideals of sustainable development undoubtedly lie with the current legislation which tends to separate social, economic and environmental objectives. The Resource Management Act (under which plans controlling subdivision and development are formulated) focuses, principally, on the environment only. Sustainable development on the other hand, focuses on objectives associated with all three. Other factors hindering the development of controls which promote more sustainable forms of residential subdivision and development, are the relative lack of research into residential design aspects and indicators of sustainability which are appropriate to New Zealand conditions, and, the general lack of awareness and acceptance by the community of planning controls which could help improve sustainability.
Keywords: New Zealand; Land subdivision -- Environmental aspects